Evaluation of a newly developed quantitative heart-type fatty acid binding protein assay based on fluorescence immunochromatography using specific monoclonal antibodies. (17th November 2015) - Kang, Keren; Wu, Peidian; Li, Wenmei; Tang, Shixing; Wang, Jihua; Luo, Xiaochun; Xie, Mingquan
Abstract : Objectives. To develop a rapid, sensitive and specific assay for quantification of serum heart-type fatty acid binding protein (H-FABP) based on immunofluorescence of specific monoclonal antibodies. Design and Methods. We generated novel H-FABP-directed monoclonal antibodies by cloning of spleen cells of mice immunized with H-FABP. Epitopes were mapped and antigen affinity was assessed by surface plasmon resonance (SPR). The H-FABP specific monoclonal antibodies were coupled to fluorescent beads and sprayed onto a nitrocellulose membrane facilitating quantification of H-FABP by immunofluorescence. Reagent cross-reactivity, interference resistance, accuracy and sensitivity were examined. A total of 103 clinical samples were used to compare the sensitivity and specificity of the new assay to a commercially available Randox kit. Results. This new assay could be finished within 15 min, with sensitivity reaching 1 ng/ml. In a trial of 103 clinical serum samples, the new testing kit results were highly correlated with those from the Randox kit (R 2 = 0.9707). Using the Randox kit as the reference kit, the sensitivity of the new assay was 98.25%, and specificity was 100%. Conclusions. An immunofluorescence-based H-FABP assay employing novel monoclonal antibodies could rapidly, specifically and sensitively detect H-FABP in serum samples, providing an effective method for rapid clinical assessment of H-FABP index in the clinic.